Bio-based flame retardants derived from forest industry — An approach towards circular economy - Sritama Mukherjee; Khan Mohammad Ahsan Uddin; Irina Turku; Anti Rohumaa; Juha Lipponen (Resources, Environment and Sustainability)
Several environmental studies on conventional flame retardants (FR) have shown them as presistent chemicals that may end up being environmental and health hazards. The advancement of eco-friendly FRs is accelerating due to the needs of improved safety and environmental sustainability. Developing bio-based FR composite materials is crucial due to their regenerable resources, low toxicity, controllable biodegradability, and versatility in application. This review examines recent advancements in utilizing forest industry products, including cellulose and nanocellulose, along with byproducts like lignin and hemicellulose. It also addresses valorized organic waste streams of pulp industries, such as tannins and biopolyols, in the creation of materials that exhibit flame retardancy in polymers and textiles. The review demonstrates functionalization methodologies, qualitative and quantitative characterization carried out on their flame retardant properties following an overview of the FR mechanisms. Finally, the opportunities and challenges for the future development of bio-based FRs are briefly identified, emphasizing on the need of utilizing waste materials as chemical precursors that can alleviate prevailing ecological concerns and open a new set of possibilities in material development in a circular economy.